2017
DOI: 10.3390/w9030212
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring, Restoration, and Source Water Protection: Canadian Community-Based Environmental Organizations’ Efforts towards Improving Aquatic Ecosystem Health

Abstract: Abstract:In Canada, environmental monitoring has been the responsibility of government for decades; however, funding cutbacks have left many agencies unable to provide comprehensive coverage. This has stimulated a rise in community-based water monitoring (CBWM) organizations. These organizations, operating at multiple scales, have tasked themselves with monitoring aquatic ecosystems. Additionally, they often engage in restoration projects stemming from their monitoring work. Despite the growing abundance of CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Recent studies have shown that engaging the public in community-based water monitoring can be a viable option when government funding declines. However, these types of programs still need to be provided with adequate financial, institutional, social and technical/human capacity to succeed [42]. Human capacity has already been diminished from its original level in the preliminary phases of the creation of the source protection plans.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that engaging the public in community-based water monitoring can be a viable option when government funding declines. However, these types of programs still need to be provided with adequate financial, institutional, social and technical/human capacity to succeed [42]. Human capacity has already been diminished from its original level in the preliminary phases of the creation of the source protection plans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as most human territories have no hydrological boundaries, a CBWM network can help involve other groups or communities within co-management schemes [23,25], when local decisions are being made. In practice, CBWM can generate data on long term trends and seasonal changes in order to create best-management practices that improve the control of soil erosion [26], protection of clean water bodies [26], groundwater management [27], and restoration activities [28][29][30], particularly in regions for which water data are lacking or difficult to access [26]. However, the establishment of CBWM faces a number of credibility challenges, given the low resolution of some monitoring tests used and that the citizens collecting the data may lack technical accreditation.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other resource monitoring, CBWM generates data that local communities and other stakeholders can use almost immediately to understand the effects of their activities on their territory [34]. Databases register the long-term behavior and trends, while single monitoring sessions allow CBWM to work as an early-warning system for local and regional stakeholders [25,28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies monitoring fishways have primarily been conducted in the United States, Canada, and Australia [21][22][23][24]. A representative example is the monitoring of fish using a fishway through visual monitoring and video recording, but a significant limitation of these techniques is that visibility varies greatly depending on the turbidity or transmittance of the water [25].…”
mentioning
confidence: 99%